Pengaruh Model Pembelajaran Sentra Peran Terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun di TK Islam Al-Khalifa Solerejo Mojowarno Jombang - Lailina Farikha; Muhammad Busyro Karim; Yulias Wulani Fajar; Ratna Nila Puspitasari (PG-PAUD Trunojoyo, 2018)
The purpose of this study was to determine the effect of learning models of role Centers on speech capabilities of child aged 5-6 years old at Al-Khalifa Islamic Kindergarten Ngepung backwoods, Solorejo Village, District Mojowarno, Jombang Regency. This research uses quantitative approach by using Experimental method with design pre-experimental research design(nondesigns) Type of one-grouppre-testpost-test.The subject of this study is a child aged 5-6 years old in Islamic Kindergarten Al-Khalifa Jombang as many as 17children’s which is representative from the whole number of research. Data collecting technique through the observation and documentation. By using t data experiment analysis  (T-Test). The result of data analysis is obtained r = 0,55 and t-test obtained grade t-count Amount -0,88 and t-table 2,178. Then t-table is bigger than t-count(-2,178 -0,88), if t-table t-count H is accepted on standard of significanse 5% which means there is significant influence between learning model of role center to child's speaking ability.